2012
DOI: 10.1016/j.ijgo.2012.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth in cases of severe acute maternal morbidity

Abstract: In Nigeria, SAMM was found to be associated with an unacceptably high rate of stillbirth. Strategies to improve fetal surveillance among women with SAMM are necessary to address the excessively high incidence of stillbirth among these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
3
8
0
1
Order By: Relevance
“…The result of this Metaanalysis showed that the magnitude of still birth is higher among women who developed maternal near miss than those who deliver without complications. The result was consistent with studies conducted elsewhere that tried to investigate the risk of still birth among maternal near miss cases [12,13,20,30]. Possible explanation for this is that, the health of the mother during pregnancy and delivery is closely linked to survival of the newborn and pregnancy complications or maternal diseases are the main cause of still birth [11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of this Metaanalysis showed that the magnitude of still birth is higher among women who developed maternal near miss than those who deliver without complications. The result was consistent with studies conducted elsewhere that tried to investigate the risk of still birth among maternal near miss cases [12,13,20,30]. Possible explanation for this is that, the health of the mother during pregnancy and delivery is closely linked to survival of the newborn and pregnancy complications or maternal diseases are the main cause of still birth [11].…”
Section: Discussionsupporting
confidence: 90%
“…In some of the African countries like Gambia, Nigeria and Sudan a higher risk of still birth was also observed among women of near miss when compared to women without near miss [17][18][19][20]. Hence, this is indicative of the link between still birth and maternal near miss.…”
mentioning
confidence: 93%
“…These findings cannot necessarily be extrapolated to lower‐resource settings, with significant restrictions in human resources, diagnostic capacity, and availability of obstetric interventions, however. The existing studies of perinatal mortality in LMICs have generally been limited in size (single or few institutions) and power (unable to consider stillbirth and early neonatal death as separate outcomes), despite accounting for 98% of the global burden. Previous large epidemiological surveys of perinatal deaths in LMICs have not captured data on maternal complications .…”
Section: Introductionmentioning
confidence: 99%
“…Maternal complications explain many severe fetal morbidities and mortalities during delivery, and thus appropriate and timely management of these complications has the potential to avoid many adverse fetal outcomes . The large disparity in stillbirth rates seen in maternal near‐miss cases across different countries, from 3.8% in Finland to as high as 46% in low‐ to middle‐income countries, is probably attributable to substandard management of complications. However, measurement challenges prevail in low‐resource settings, restricting a direct comparisons of rates across different settings.…”
Section: Introductionmentioning
confidence: 99%
“…in low-to middle-income countries, [10][11][12][13][14] is probably attributable to substandard management of complications. However, measurement challenges prevail in low-resource settings, 15 restricting a direct comparisons of rates across different settings.…”
Section: Introductionmentioning
confidence: 99%